HIV pre-exposure prophylaxis adherence test using reverse transcription isothermal amplification inhibition assay. Issue 13 (17th March 2022) - Zhang, Jane Y.; Zhang, Yu; Bender, Andrew T.; Sullivan, Benjamin P.; Olanrewaju, Ayokunle O.; Lillis, Lorraine; Boyle, David; Drain, Paul K.; Posner, Jonathan D.
Abstract : We report on a probabilistic isothermal nucleic acid amplification assay for measuring a common medication in HIV prevention and treatment. Expanded access to routine HIV drug adherence testing is a crucial tool in improving the HIV care continuum. Abstract : Current HIV antiretroviral therapy (ART) or pre-exposure prophylaxis (PrEP) therapy adherence monitoring relies on either patient self-reported adherence or monitored drug dispensing, which are not reliable. We report a proof-of-concept adherence monitoring assay which directly measures nucleotide reverse transcriptase inhibitor (NRTI) concentration using a reverse transcription isothermal amplification inhibition assay. We measure the concentration of Tenofovir diphosphate (TFV-DP) – an NRTI that functions as a deoxyadenosine triphosphate (dATP) analog and long-term adherence marker for PrEP – by measuring the inhibition of the reverse transcription of an RNA template. The completion or inhibition of reverse transcription is evaluated by recombinase polymerase amplification (RPA), an isothermal nucleic acid amplification assay commonly used for point-of-care diagnostics. We present and validate a model that predicts the amplification probability as a function of dATP and TFV-DP concentrations, nucleotide insertion sites on the RNA template, and RNA template concentration. The model can be used to rationally design and optimize the assay to operate at clinically relevant TFV-DP concentrations. We provide statistical analysis that demonstrates how the assay may be used as a qualitative or semi-quantitative tool for measuring adherence to NRTI drugs and used to support patient compliance. Due to its simple instrumentation and short runtime (<1 hour), this assay has the potential for implementation in low-complexity laboratories or point-of-care settings, which may improve access to ART and PrEP adherence monitoring.